2005
DOI: 10.3748/wjg.v11.i39.6096
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-associated gastric carcinoma: Evidence of age-dependence among a Mexican population

Abstract: Among Latin-American countries, Mexico has the lowest frequency of EBVaGC. Indeed, the Mexican population >50 years of age was selectively affected. Ethnic variations are responsible for the epidemiologic behavior of EBVaGC among the worldwide population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
51
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 36 publications
13
51
3
2
Order By: Relevance
“…Consistent to the previous studies males showed higher risk of infection compared to females [20,21], metaanalysis of 15,952 cases shown that EBV-positive in GC occur more frequently in male than in female patients [22]. Most studies indicated that lifestyle or occupational factors may exist among males [10,23,24].The highest incidence of EBV in Gastric cancer was at (50-59) year age [21,25].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Consistent to the previous studies males showed higher risk of infection compared to females [20,21], metaanalysis of 15,952 cases shown that EBV-positive in GC occur more frequently in male than in female patients [22]. Most studies indicated that lifestyle or occupational factors may exist among males [10,23,24].The highest incidence of EBV in Gastric cancer was at (50-59) year age [21,25].…”
Section: Discussionsupporting
confidence: 69%
“…Most studies indicated that lifestyle or occupational factors may exist among males [10,23,24].The highest incidence of EBV in Gastric cancer was at (50-59) year age [21,25]. Occurrence in elderly persons and male predominance are common in EBV-associated gastric carcinomas [26].…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding has been reported for Epstein-Barr virusassociated gastric carcinomas. 37 Furthermore, in this study, we found that JCV is more commonly detected in intestinal histological type of gastric carcinomas (P ¼ 0.04). This finding seems in harmony with the known description in literature.…”
Section: Discussionmentioning
confidence: 53%
“…In our study, EBV latent infection antibodies were not associated with gastric cancer risk. These differences may be due to infection by different EBV strains, which are believed to influence EBV-infected gastric cancer worldwide in combination with different environmental factors (Herrera-Goepfert et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Epstein -Barr virus infection is believed to be related to 5 -16% of gastric adenocarcinomas, with variations across populations (Burgess et al, 2002;Macsween and Crawford, 2003;Correa et al, 2004;Herrera-Goepfert et al, 2005). Most studies to date have been tumour tissue-based, providing information about the role of EBV in gastric carcinogenesis, but providing limited information on the association between EBV infection and gastric cancer, particularly adenocarcinoma -the most prominent histology (Tokunaga and Land, 1998;Chang and Kim, 2005;Akiba et al, 2008).…”
mentioning
confidence: 99%